Cytostatic resistance profile of the sulfur mustard resistant keratinocyte cell line HaCaT/SM. (1st September 2018) - Schmidt, Annette; Wolf, Markus; Rothmiller, Simone; Worek, Franz; Steinritz, Dirk; Thiermann, Horst
Highlights: HaCaT/SM cells are resistant to sulfur mustard. Surprisingly HaCaT/SM are also resistant to other cytostatic drugs. The highest increase can surprisingly be observed for cisplatin, a DNA crosslinker. Abstract: Background: The cell line HaCaT/SM was developed as a sulfur mustard (SM) resistant cell line from the human keratinocyte cell line HaCaT. This cell line was established to learn more about the effect of SM and possible therapeutic approaches to counteract the cytotoxic effects of SM. The aim of this study was to clarify whether the SM-resistant cell line HaCaT/SM exhibit also resistance to other alkylating agents or cytotoxic drugs with different mechanism of action. Material and method: The chemosensitivity of SM-resistant human keratinocyte cell line HaCaT/SM and the original cell line HaCaT were tested using the XTT assay. Nine cytotoxic drugs from five different substance groups were investigated. Results: HaCaT/SM showed a significant increase in resistance against all tested drugs. From the substance class of the alkylating agents, HaCaT/SM showed the strongest resistance increase against chlorambucil (1.7 fold increase). Whereas over all substances strongest increase was observed against cisplatin (5.1 fold increase). Discussion: The highest resistance was observed for cisplatin. The SM resistant cells revealed changes in the miRNA profile as described before. The resistance to cisplatin is also connected to a specific miRNA profile. Interestingly, changes of miRNA-203 and miRNA-21 levels were found in HaCaT/SM as well as in cisplatin resistant cells. It is therefore conceivable that the same resistance pathways are involved for both substances.